Clinical and immunological characterization of a Netherton syndrome infant with a large SPINK gene cluster deletion and a c.1258A>G polymorphism in SPINK5 - Guan, Yaning; Li, Qian; Liu, Yongjing; Zhang, Pingping; Huang, Maolin; Guo, Yimin; Chen, Jing; Chen, Yan; Du, Zuochen; Huang, Pei (Frontiers in Immunology, 2025)
IntroductionNetherton syndrome (NS) is a rare autosomal recessive disorder caused by mutations in the SPINK5 gene, which encodes the serine protease inhibitor LEKTI. It is characterized by congenital ichthyosis, hair shaft abnormalities, and atopic manifestations. Previous reports suggest that intravenous immunoglobulin (IVIG) may provide partial clinical benefit in NS. Here, we report the clinical and immunological characterization of an infant with NS effectively treated with IVIG therapy. MethodsClinical information was collected and reviewed from a 1-year-6-month-old boy presenting with NS. Hair shaft abnormalities were examined by scanning electron microscopy. Pathogenic variants in SPINK5 were identified using whole-exome and Sanger sequencing. Protein expression was assessed by Western blotting and ELISA. Peripheral lymphocyte subsets were analyzed by flow cytometry, and cytokine levels were evaluated with the Olink® Target 48 Cytokine panel. ResultsThe patient presented with typical clinical manifestations of NS. Genetic analysis identified a novel heterozygous deletion spanning the SPINK5 gene (chr5:147,443,561-147,719,327), together with the c.1258A>G (p.K420E) polymorphism. LEKTI expression was markedly decreased, consistent with the genetic findings. Immune profiling revealed markedly reduced unswitched memory and marginal zone-like B cells, increased naïve B cells, and elevated γδ T cells compared with healthy controls. Cytokine analysis showed significantly increased levels of multiple pro-inflammatory cytokines, including TGFA, IL17 family members, CXCL8, CCL2, TNF, CCL19, and IL18. Following IVIG therapy, the patient demonstrated significant clinical improvement, with recovery of skin manifestations, and partial normalization of lymphocyte subsets and cytokine levels, indicating restoration of immune regulation. DiscussionThis study reports a novel compound heterozygous SPINK5 mutation in an infant with NS, comprising a large deletion and c.1258A>G polymorphism, resulting in LEKTI deficiency and immune dysregulation. IVIG therapy effectively alleviated clinical symptoms and restored immune balance, highlighting its potential as a therapeutic option for NS and related immunodeficiency disorders.